RESOURCE ALLOCATION USING SJF AND DOMAIN SPECIFIC STORAGE TECHNIQUES - J, Ramaprabha; Reddy, T. Anurag; Kumararaja, Ankam (International Journal of Psychosocial Rehabilitation, 2020)
Load Balancing is even distribution of excessive workloads among all nodes to achieve better resource and service utilization. Load-Balancer is assigned with the task of receiving and distributing the load to the DATACENTRES.Proposed model gives an effective load balancer to stay away from blockage and overburdening of server at the data center. We utilized modified SJF algorithm to implement Dynamic balancing of severs. It is utilized for accomplishing a superior assistance provisioning and resource usage proportion, subsequently improving the general performance of the system.The Cloud agents exploit Cloud Providers. The Cloud providers assist the users with discount pricing schemes through online . Modified Sjf A and K-Means algorithm together used to implement the Scheduling or resource allocation . For file storage and retrieval the data is encrypted with the help of AES method and sent to cloud. In information recuperation, the documents are relocated from the virtual machines to cloud named CloudMe for data backup.Also to dissect which particular kind of records are every now and then accessed by the clients we implemented Domain Specific Storage. We have set a charging unit which break down and gives which specific area is every now and then accessed and depending on that virtual machine capacity is expanded/diminished. Likewise the charging unit gives the expense to surveying the records or the data-files.